Acute Respiratory Distress Syndrome in Patients with Subarachnoid Hemorrhage: Incidence, Predictive Factors, and Impact on Mortality. Issue 2 (April 2023) - Feldstein, Eric; Ali, Syed; Patel, Smit; Raghavendran, Keshav; Martinez, Erick; Blowes, Leah; Ogulnick, Jonathan; Bravo, Michelle; Dominguez, Jose; Li, Boyi; Urhie, Ogaga; Rosenberg, Jon; et al.
Introduction: Acute respiratory distress syndrome (ARDS) is a known predictor of poor outcomes in critically ill patients. We sought to examine the role ARDS plays in outcomes in subarachnoid hemorrhage (SAH) patients. Prior studies investigating the incidence of ARDS in SAH patients did not control for SAH severity. Hence, we sought to determine the incidence ARDS in patients diagnosed with aneurysmal SAH and investigate the predisposing risk factors and impact upon outcomes. Methods: A retrospective cohort study was conducted using the National Inpatient Sample (NIS) database for the years 2008 to 2014. Multivariate stepwise regression analysis was performed to identify the risk factors and outcome associated with developing ARDS in the setting of SAH. Results: We identified 170, 869 patients with non-traumatic subarachnoid hemorrhage, of whom 6962 were diagnosed with ARDS and of those 4829 required mechanical ventilation. ARDS more frequently developed in high grade SAH patients (1.97 ± 0.05 vs. 1.15 ± 0.01; p < 0.0001). Neurologic predictors of ARDS included cerebral edema (OR 1.892, CI 1.180–3.034, p = 0.0035) and medical predictors included cardiac arrest (OR 4.642, CI 2.273–9.482, p < 0.0001) and cardiogenic shock (OR 2.984, CI 1.157–7.696, p = 0.0239). ARDS was associated with significantly worse outcomes (15.5% vs. 52.9% discharged home, 63.0% vs. 40.8% discharged to rehabilitation facility and 21.5% vs. 6.3% in-hospital mortality). Conclusion: Patients with SAH who developed ARDS were less likely to be discharged home, more likely to need rehabilitation and had a significantly higher risk of mortality. The identification of risk factors contributing to ARDS is helpful for improving outcomes and resource utilization.